Saltwater Intrusion in a Mediterranean Delta Under a Changing Climate. Issue 2 (5th February 2021) - Bellafiore, Debora; Ferrarin, Christian; Maicu, Francesco; Manfè, Giorgia; Lorenzetti, Giuliano; Umgiesser, Georg; Zaggia, Luca; Levinson, Arnoldo Valle
Abstract: Saltwater intrusion (SWI) in deltas, estuaries, and other coastal areas represents a pressing problem affecting the sustainability of freshwater resources. Observations and numerical experiments are used to investigate SWI in the surface waters of the Italian's largest river delta (the Po Delta) under low discharge conditions. The model successfully reproduced the observed salinity variations along main river branches and in the delta lagoons and investigated fresh and saltwater dynamics during the entire summer 2017. The numerical model is used to explore the hydrological response of the delta system to climate change. The relative effect of controlling factors on saltwater penetration, such as sea‐level rise (SLR), air‐sea fluxes, and reduction of river discharge, was evaluated. Results suggest that changes driven by climate and SLR will exacerbate SWI in the surface waters of the Po Delta system. Extent of SWI in the major river branch is projected to increase up to 80% further into the river. Persistence of SWI at the same site is expected to increase 100% longer. Moreover, additional synthetic simulations were used to investigate the sensitivity of SWI to several river discharges and relative SLR values, highlighting the effects of the two factors in the delta. Such results show different combinations of river discharge and relative SLR values that represent possible scenarios, and are important for managing SWI in river‐sea systems affected by both climatic and anthropogenic factors such as discharge changes from dam construction, land use, and irrigation. Key Points: Along‐channel saltwater fluxes are controlled by advective and shear dispersion fluxes, and influenced by branch morphology Future saltwater intrusion (SWI) is projected to increase up to 80% further into the river, while persistence up to 100% longer River discharge reduction is expected to affect SWI more than sea‐level rise